2019
DOI: 10.1021/acsnano.9b04704
|View full text |Cite|
|
Sign up to set email alerts
|

Remodeling of a Cell-Free Vascular Graft with Nanolamellar Intima into a Neovessel

Abstract: Advances in cardiovascular materials have brought us improved artificial vessels with larger diameters for reducing adverse responses that drive acute thrombosis and the associated complications. Nonetheless, the challenge is still considerable when applying these materials in small-diameter blood vessels. Here we report the biomimetic design of an acellular small-diameter vascular graft with specifically lamellar nanotopography on the luminal surface via a modified freeze-cast technique. The experimental find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…This effect was subsequently confirmed in human patients where microgrooved stents were found to be associated with significantly lower levels of neointimal hyperplasia (abnormal proliferation and migration of SMCs leading to restenosis) and appeared to promote a more homogeneous surface healing of the stent compared to standard bare metal stents (Vesga et al, 2017). More recently, a freeze-cast technique has been used to develop a small-diameter vascular graft with luminal nano-grooves; this surface was able to induce EC alignment and reduce the number of adherent platelets (Wang et al, 2019). In addition, numerical simulations revealed that this lamellar topography reduced blood flow disturbance compared to a random topography.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…This effect was subsequently confirmed in human patients where microgrooved stents were found to be associated with significantly lower levels of neointimal hyperplasia (abnormal proliferation and migration of SMCs leading to restenosis) and appeared to promote a more homogeneous surface healing of the stent compared to standard bare metal stents (Vesga et al, 2017). More recently, a freeze-cast technique has been used to develop a small-diameter vascular graft with luminal nano-grooves; this surface was able to induce EC alignment and reduce the number of adherent platelets (Wang et al, 2019). In addition, numerical simulations revealed that this lamellar topography reduced blood flow disturbance compared to a random topography.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…The presence of a cross-bridging motif would favor the binding among the diverse sticky-end sequences; in addition to the degradation of the complex structures by RNases, this allows the creation of complex-shaped droplets. Although this project's scope seems to tackle a drug delivery matter, it could allow the development of regenerative medicine approaches, such as bioactive molecule encapsulation within cell-free tissue-engineered vascular drafts [14,112].…”
Section: Nucleic Acid-derived Polymersmentioning
confidence: 99%
“…To give an example, Muller et al used biomaterials with solid fractions, such as bioceramics or nanoparticles for bone or cartilage tissue regeneration. Because of the presence of two different materials, the particles and the hydrogel produce inconsistent dispersion of 14 Advances in Polymer Technology particles; thus, the printing or the formation of the desired morphology is difficult to achieve. The group solved this issue by the use of gellan gum methacrylate, hyaluronic acid methacrylate with hydroxyapatite crystals or particles that enhanced the ink's printability.…”
Section: Supramolecular Biopolymers For Bioprintingmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly (styrene) and poly (4-bromostyrene) consisting of nanohills 13 and 35 nm in height presented greater adhesion and better spreading of HUVECs and human microendothelial cells. The best endothelialized poly (styrene) and poly (4-bromostyrene) surfaces of 13 nm nanohills exhibited the lowest monocyte and granulocyte adherence [89,90], and the oriented nanotopography surface and the lower depth structure (< 40 nm) always exhibited fewer platelets adhesion [91,92]. A comparison of gradient nanopatterned plates consisting of nanopillars with different diameters ranging from 120-200, 200-280, to 280-360 nm has shown that the cytoskeletal integrity and focal adhesion of human endothelial colony-forming cells (hECFCs) on nanopatterned plates are better than PLLA nanofibrous membrane…”
Section: Dimensionsmentioning
confidence: 99%